Pengalaman Informasi Pengguna Akun Autobase Twitter @Sbmptnfess sebagai Sumber Informasi bagi Calon Mahasiswa - Salsabilla Risna Azzahra; Athanasia Octaviani Puspita Dewi (Prodi S1 Ilmu Perpustakaan dan Informasi, Fakultas Ilmu Budaya, Universitas Diponegoro, 2023)
Information experience explores how individuals engage with information and how they relate to information in everyday life. This study discusses the information experience of users of the Twitter @sbmptnfess autobase account as a source of information for prospective students during the selection period to enter college. The purpose of this research is to know how the information experience of users of the autobase Twitter account @sbmptnfess as a source of information in preparing for college entrance selection for prospective students. The research method used is a qualitative method with a phenomenological approach, data collection is done using passive observation and semi-structured interviews. Informants were selected using a purposive sampling technique as many as 12 informants. Data analysis using thematic analysis. The research results consist of 4 themes, that is the use of Twitter and autobase as a source of information, information needs and fulfillment of the information needs of prospective students, Twitter autobase as a source of information and experience using an autobase Twitter account as a source of information. The results of the study show that the information experience of prospective students consists of experience of choosing the autobase account @sbmptnfess as a source of information; the involvement experiences of prospective students in autobase accounts consisting of sending menfess, commenting and sharing information; the feelings of prospective students when using an autobase account consist of feeling happy because they can share information and hope that their information needs can be fulfilled through an autobase account; experience feelings after using an autobase account consisting of feeling happy, relieved, and satisfied because information needs can be fulfilled; experience in using an autobase account as a source of information consists of helping, impressing, being able to ask questions and answers, and experience awareness. Information experience by prospective students shows that the autobase account is used as a source to find information by considering the accuracy of the information obtained.